THE PENAL CODE OF THE STATE OF MINNESOTA TO TAKE EFFECT JANUARY 1, A. D. 1886, at 127 (1885) §334 - (:unkn) unknown (General Publisher, 1885)
Prohibited the carry or possession with intent to use against another any slung-shot, sand-club, metal knuckles, dagger, dirk, knife, pistol, or other firearm, or any dangerous weapon. Violators guilty of misdemeanor.
--
Keywords: CARRY - INTENT TO COMMIT CRIME